Analisis Strategi Maintenance Marketingpt Demitra Karsa Perdana terhadap Klien: Tinjauan Dari Tahun 2018-2023 - Claudia Puspita Sari; Eddy Haristiani (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to answer the research question: how are maintenance marketing strategies implemented by PT Demitra Karsa Perdana in maintaining client relationships during the period 2018–2023? A qualitative research approach was employed by combining in-depth interviews, direct observations, and literature review. The primary data were collected from key company executives and one strategic client, while secondary data were obtained from internal documents, including manpower growth and client satisfaction surveys. The findings reveal that the company’s maintenance marketing strategies are supported by four main factors: providing optimal services tailored to client needs, building strong partnerships with stakeholders such as the Indonesian Armed Forces and Police, complying with client-specific security standards, and applying technology through the barcode patrol system. Client satisfaction surveys consistently showed that most respondents were categorized as satisfied to very satisfied, which is in line with the steady increase in both client numbers and manpower throughout the study period. The results highlight that the success of maintenance marketing is not solely determined by operational performance, but by the synergy of strategic communication, technological adaptation, and relational approaches. This research contributes practical insights for other security service companies in designing client retention strategies and offers academic value by enriching literature on Customer Relationship Management (CRM) in the security service sector.